Differential modulation of gene expression in the NMDA postsynaptic density of schizophrenic and control smokers - Mexal, S.; Frank, M.; Berger, R.; Adams, C.E.; Ross, R.G.; Freedman, R.; Leonard, S. (Brain research. Molecular brain research., 2005)
Nicotine is known to induce the release of multiple neurotransmitters, including glutamate and dopamine, through activation of nicotinic receptors. Gene expression in the N-methyl- d-aspartate postsynaptic density (NMDA-PSD), as well as other functional groups, was compared in postmortem hippocampus of schizophrenic and nonmentally ill smokers and nonsmokers utilizing a microarray and quantitative RT-PCR approach. The expression of 277 genes was significantly changed between all smokers and nonsmokers. Specific gene groups, most notably genes expressed in the NMDA-PSD, were prevalent among these transcripts. Analysis of the interaction between smoking and schizophrenia identified several genes in the NMDA-PSD that were differentially affected by smoking in patients. The present findings suggest that smoking may differentially modulate glutamatergic function in schizophrenic patients and control subjects. The biological mechanisms underlying chronic tobacco use are likely to differ substantially between these two groups.